Diving Technic Improvment Of Compressor Diver At Kondang Merak, Malang Using Scuba - oktiyas muzaky Luthfi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
Kondang Merak laid on South of Malang facing of Indian Ocean. This area had small fisheries village which inhibited by 30 families. 12 fisheries worked as compressor diver who collect lobster and abalone surrounding of reef in Kondang Merak. Those commodity usually hand collected by fishermen using compressor dive. During dive fishermen ignored depth, bottom time or tools that they used. We are introduced self contained underwater breathing apparatus (SCUBA) training for fishermen. Aims of this training were to give: knowledge about diving and physical and environment aspect influence dive activity; technical use of SCUBA and caring for diving apparatus. Good skill and technic will obviate fishermen from decompression sickness disease (DCS) and nitrogen narcosis which have dangerous impact for health of fisherman in Kondang Merak. Keywords: Kondang Merak, compresor diver, SCUBA, DCS, compressor